Integration of NLP (Natural Language Processing)-Based Technology in Japanese Language Learning - Launingtia, I Gusti Ayu Niken; I Nengah Suandi; Ida Bagus Putrayasa (Journal of Practice Learning and Educational Development, 2025)
The advancement of Natural Language Processing (NLP) technology has significantly impacted the methods of foreign language education, including Japanese. This study aims to analyze the implementation of NLP-based technology in enhancing the efficiency and effectiveness of Japanese language learning for non-native learners. Using a literature review and content analysis approach, this article examines various educational applications that utilize NLP features such as automatic feedback, pronunciation training, and real-time syntactic and semantic analysis. The findings suggest that NLP can enrich the learning experience by offering personalized support and adaptive learning paths. However, challenges such as cultural context limitations and dependency on native-speaker-oriented data remain. This research provides insights and recommendations for curriculum developers and educational technology designers in optimizing NLP-based tools for Japanese language instruction.